Synthesis and high temperature thermoelectric properties of Yb0.25Co4Sb12-(Ag2Te)x(Sb2Te3)1−x nanocomposites - Zheng, Jin; Peng, Jiangying; Zheng, Zhexin; Zhou, Menghan; Thompson, Emily; Yang, Junyou; Xiao, Wanli (Frontiers in Chemistry, 2015)
Nanocomposites are becoming a new paradigm in thermoelectric study: by incorporating nanophase(s) into a bulk matrix, a nanocomposite often exhibits unusual thermoelectric properties beyond its constituent phases. To date most nanophases are binary, while reports on ternary nanoinclusions are scarce. In this work, we conducted an exploratory study of introducing ternary (Ag2Te)x(Sb2Te3)1-x inclusions in the host matrix of Yb0.25Co4Sb12. Yb0.25Co4Sb12 - 4wt% (Ag2Te)x(Sb2Te3)1-x nanocomposites were prepared by a melting-milling-hot-pressing process. Microstructural analysis showed that poly-dispersed nanosized Ag-Sb-Te inclusions are distributed on the grain boundaries of Yb0.25Co4Sb12 coarse grains. Compared to the pristine nanoinclusion-free sample, the electrical conductivity, Seebeck coefficient, and thermal conductivity were optimized simultaneously upon nanocompositing, while the carrier mobility was largely remained. A maximum ZT of 1.3 was obtained in Yb0.25Co4Sb12-4wt% (Ag2Te)0.42(Sb2Te3)0.58 at 773 K, a ~ 40% increase compared to the pristine sample. The electron and phonon mean-free-path were estimated to help quantify the observed changes in the carrier mobility and lattice thermal conductivity.